A RARE CAUSE OF THE CAVERNOUS SINUS SYNDROME AND AN OLD CLINICAL LESSON RELEARNT. Issue 11 (9th October 2013) - Ng, Yi Shiau; Davenport, Richard; Broom, Angus
Abstract : Introduction: Cavernous sinus syndrome is rare, characterised by ophthalmoplegia, orbital congestion plus proptosis, trigeminal sensory loss, and sympathetic disturbance (Horner's syndrome). 1 In this case, an elderly man presented with painful left 6th and 3rd nerve palsies. Investigations revealed an aggressive lymphoma to be the cause. Although tumour is the most common cause of cavernous sinus syndrome 2, it is unusual for systemic lymphoma to present in this way without other systemic symptoms. Case description: An 82 year old man presented with subacute progressive left painful ophthalmoplegia and ptosis which clinically was consistent with 3rd and 6th cranial nerve palsies. He was otherwise well. His presentation blood tests included a normal full blood count, renal and liver function, erythrocyte sedimentation rate and serum calcium level. CT head with contrast including angiographic and venographic sequences was reported normal. His symptoms were attributed to microvascular cause. He represented as his symptoms evolved, and MRI head revealed an enhancing left cavernous sinus mass. In retrospect, this abnormality was evident on his CT head scan performed two weeks previously. His serum LDH was now raised and his CT body scan showed diffuse lymphadenopathy. Biopsy of an axillary lymph node confirmed small lymphocytic lymphoma. However, it was felt that this was insufficiently aggressive to account for his intracranial lesion, and thus he underwent biopsy of the cavernous sinus mass. Histology confirmed the clinical suspicion of Richter's syndrome: a rare transformation of low–grade to high–grade non–Hodgkin lymphoma. He was treated with dexamethasone and radiotherapy. Discussion: Our case proved to be due to a rare cause, but it illustrates the importance of reviewing "normal" imaging when there is a strong clinical suspicion of a structural abnormality. Cavernous syndrome can be the presentation of haematological malignancy or other metastatic disease. Figure 1 (Left): CT head with contrast Figure 2 (Right): MRI head with gadolinium.